D-dimer Thresholds to Exclude Pulmonary Embolism among COVID-19 Patients in the Emergency Department: Derivation with Independent Validation. (August 2022) - Bledsoe, Joseph R.; Knox, Daniel; Peltan, Ithan D.; Woller, Scott C.; Lloyd, James F.; Snow, Gregory L.; Horne, Benjamin D.; Connors, Jean M.; Kline, Jeffrey A.
Objective: To derive and validate a D-dimer cutoff for ruling out pulmonary embolism (PE) in COVID-19 patients presenting to the emergency department (ED). Methods: A retrospective cohort study was performed in an integrated healthcare system including 22 adult ED's between March 1, 2020, and January 31, 2021. Results were validated among patients enrolled in the RECOVER Registry, representing data from 154 ED's from 26 US states. Consecutive ED patients with laboratory confirmed COVID-19, a D-dimer performed within 48 h of ED arrival, and with objectively confirmed PE were compared to those without PE. After identifying a D-dimer threshold at which the 95% confidence lower bound of the negative predictive value for PE was higher than 98% in the derivation cohort, it was validated using RECOVER registry data. Results: Among 3978 patients with a D-dimer result, 3583 with confirmed COVID-19 infection were included in the derivation cohort. Overall, PE incidence was 4.1% and a D-dimer cutoff of< 2 μ/mL (2000 ng/mL) was associated with a NPV of 98.5% (95% CI = 98.0%−98.9%). In the validation cohort of 13, 091 patients with a D-dimer, 7748 had confirmed COVID-19 infection, and the PE incidence was 1.14%. A D-dimer cutoff of< 2 μ/mL was associated with a NPV of 99.5% (95% CI = 99.3%−99.7%). Conclusion: A D-dimer cutoff of< 2 μ/ml was associated with a high negative predictive value for PE among patients with COVID-19. However, the resultant sensitivity for PE result at that threshold without pre-test probability assessment would be considered clinically unsafe.